Moby Dick, or, The white whale - "Mccaughrean, Geraldine" (Oxford Universty Press: Oxford, 2002)
Moby Dick is a vast and dangerous white whale. An enemy for many years after the whale bit off his leg, the crazed Captain Ahab is obsessed with his quarry. The author is one of the most distinguished living children's authors. She has won The Carnegie Medal, The Whitbread Children's Novel Award (twice), and The Guardian Children's Fiction Award.
Keywords: Sea stories